How to promote the application of green pesticides by farmers? Evolutionary game analysis based on “government–farmer–consumer” - Wang, Xiaofeng; Cui, Xiaojun; Sun, Xiaolong (Frontiers in Environmental Science, 2024)
Green pesticide use, as a key means to reduce pesticide use, plays a crucial role in promoting environmental and food safety. However, the effectiveness of green pesticide use policies in China falls short of expectations. Existing research mainly examines the policy promotion issues of green pesticide use from a static and single agent perspective. However, green pesticide use behaviour is a dynamic process influenced by multiple actors, including the government, farmers and consumers. This paper builds an evolutionary tripartite game model of the government, farmers and consumers from the perspective of dynamic strategy evolution, and explores the evolutionary conditions that affect the stability of the tripartite game strategy during green pesticide application. The results show that: (1) Through different partnership models, the government, farmers and consumers can evolve to a stable state. (2) Keeping the government's regulatory intensity in the market of green agricultural products at a reasonable range will help farmers to apply green pesticides. (3) Users' preference for high quality vegetables will increase the market selling price of green products. (4) Maintaining the government's ecological subsidies for green pesticides will help stimulate farmers' enthusiasm for using green pesticides. Therefore, the government should appropriately strengthen ecological subsidies and market supervision, guide consumers' green consumption behaviour, and encourage farmers to use green pesticides.